Tertiary Lymphoid Organs (TLOs): Powerhouses of Disease Immunity - Changjun Yin (Frontiers Research Topics, 2017)
The immune system employs TLOs to elicit highly localized and forceful responses to unresolvable peripheral tissue inflammation. Current data indicate that TLOs are protective but they may also lead to collateral tissue injury and serve as nesting places to generate autoreactive lymphocytes. A better comprehension of these powerhouses of disease immunity will likely facilitate development to unprecedented and specific therapies to fight chronic inflammatory diseases.